Tumor accomplice: T cell exhaustion induced by chronic inflammation - Fang, Liguang; Liu, Kunjing; Liu, Cun; Wang, Xiaomin; Ma, Wenzhe; Xu, Wenhua; Wu, Jibiao; Sun, Changgang (Frontiers in Immunology, 2022)
The development and response to treatment of cancer are modulated by inflammation, and chronic inflammation promotes tumor progression and therapy resistance. This article summarizes the dynamic evolution of inflammation from acute to chronic in the process of tumor development, and its effect on T cells from activation to the promotion of exhaustion. We review the mechanisms by which inflammatory cells and inflammatory cytokines regulate T cell exhaustion and methods for targeting chronic inflammation to improve the efficacy of immunotherapy. It is great significance to refer to the specific state of inflammation and T cells at different stages of tumor development for accurate clinical decision-making of immunotherapy and improving the efficiency of tumor immunotherapy.